Natural Moisturizer Based Formulation of Green Leaf Jelly (Cyclea Barbata Miers) with Bengkoang Addition (Pachyrhizus Erosus) - Ilham, Muhammad; Harismah, Kun (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2020)
This study is aimed to know the use of green grass as a healthy alternative in preventing the occurrence of diseases caused by carcinogens and related to skincare. Sun exposure can cause various problems, especially on the skin, such as dry skin. Natural moisturizers can be the solution. Formulations of green grass jelly and bengkoang leaves can be an alternative use of natural moisturizers. One of the ingredients in green grass jelly leaves is the content of polyphenols and flavonoids contained in green grass jelly leaves can function as antioxidants. The research uses a draft of 2-Factor complete randomized design (RAL) type by using 4 treatment variations of green grass jelly formula (2.5%; 5%; 7.5%; and 10%) + Bengkoang (0%, 2.5%, 5%, 7.5%, 10%) and treatment of formulations without green grass. Â The results of the study are moisturizer based on green grass with the addition of bengkoang that has been made to meet the pH standard. Based on SNI-16-4399-1996, all samples that have been made meet the existing standards and the formulation samples that comply with the standard are F (D), ie green grass jelly concentration of 2.5% and Bengkong 5%